Socially optimal coordination: Characterization and policy implications - George-Marios Angeletos; Alessandro Pavan (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2006)
In recent years there has been a growing interest in macro models with heterogeneity in information and complementarity in actions. These models deliver promising positive properties, such as heightened inertia and volatility. But they also raise important normative questions, such as whether the heightened inertia and volatility are socially undesirable, whether there is room for policies that correct the way agents use information in equilibrium, and what are the welfare effects of the information disseminated by the media or policy makers. We argue that a key to answering all these questions is the relation between the equilibrium and the socially optimal degrees of coordination. The former summarizes the private value from aligning individual decisions, whereas the latter summarizes the value that society assigns to such an alignment once all externalities are internalized.
Keywords: C72; D62; D82; 330; dispersed information; coordination; complementarities; volatility; inertia; efficiency